Analyzing the Improvement of StudentsÔÇÖ Public Speaking Skills Through Interactive Live Audience Feedback Strategies - Silvia Djonnaidi; Difiani Apriyanti; Fitri Handayani (Ta'dib, 2025)
This qualitative case study investigated the impact of Interactive Live Audience Feedback (LAF) on the development of studentsÔÇÖ public speaking skills. Conducted in a Public Speaking course involving 60 undergraduate students from the English for Business and Professional Communication program, the study used purposeful sampling and involved two stages: an initial presentation without feedback and a re-presentation following structured verbal and nonverbal feedback from the audience. Data were collected through audience comments, reflective journals, and field notes, and then analyzed thematically. Findings showed significant improvements in four areas: eye contact, body language, presentation structure, and use of visual content, highlighting improvements in confidence, clarity, and engagement. The study suggests that live audience feedback promotes reflective and participatory learning. However, limitations include potential observer bias and uncontrolled social dynamics in the classroom. Theoretically, the study integrates LasswellÔÇÖs Communication Model, BanduraÔÇÖs Self-Efficacy Theory, and VygotskyÔÇÖs Social Development Theory to explain the feedback-learning relationship. Practically, the LAF model offers an adaptable strategy for improving communication competence in a variety of educational and professional contexts.